Relationship between motor, imitation and, early social communication skills in children with autism - hooshang Dadgar; Javad Alaghband Rad; Zahra Soleymani; Anahita Khorammi; Saman Maroufizadeh (Iranian Journal of Psychiatry, 2017)
Background: The aim of this study was investigation the association of motor skills and imitation ability with early social communication skills in children with autism spectrum disorder (ASD).